PENGUATAN PERAN MASYARAKAT DAN PEMERINTAH DESA DALAM IMPLEMENTASI PERMEN NO.6 TAHUN 2018 TENTANG PTSL - Gobel, Rahmat Teguh Santoso; Fuad, Andi M.; Sardadi, Asiv (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Complete Systematic Land Registration (Pendaftaran Tanah Sistematis Lengkap/PTSL) is a national strategic policy aimed at accelerating the legalization of land rights and establishing orderly land administration; however, its implementation at the village level is often hindered by low levels of legal literacy, unclear procedures, and incomplete documentation. In Tupa Village, Bulango Utara District, these constraints are reflected in limited public access to information and insufficient administrative readiness among residents, including deficiencies in inheritance documents, land tenure history, and boundary clarity, as well as the absence of written village guidelines for data collection, verification, and assistance in the implementation of PTSL. This community service program focuses on improving public understanding and strengthening village institutional capacity through a problema based approach within a Participatory Action Research (PAR) framework. The implementation stages included initial coordination and observation, legal counseling through interactive lectures accompanied by question-and-answer sessions and case consultations conducted on 1 October 2025, follow-up discussions with village officials, and the preparation of a draft Village Regulation (Perdes) on the Governance of PTSL Implementation. The results indicate an increase in residents’ literacy regarding the urgency of land certification, the components of physical and juridical data, PTSL administrative procedures, and practical solutions to issues such as missing documents, inherited land, and unclear boundaries; the activities also helped correct misconceptions related to registration fees. At the institutional level, the draft Village Regulation provides a more structured operational guideline, including the establishment of an implementation team, mechanisms for data collection and verification, and coordination workflows between the village administration and the National Land Agency (BPN) thereby strengthening accountability in land services and supporting the sustainability of PTSL. In conclusion, the synergy between legal education and the formulation of local regulations effectively enhances community administrative readiness while reinforcing village-level land governance. ABSTRAKPendaftaran Tanah Sistematis Lengkap (PTSL) merupakan kebijakan strategis nasional untuk mempercepat legalisasi hak atas tanah dan mewujudkan tertib administrasi pertanahan, namun implementasinya di tingkat desa sering terhambat oleh rendahnya literasi, ketidakjelasan prosedur, dan ketidaklengkapan dokumen.  Di Desa Tupa, Kecamatan Bulango Utara, hambatan tersebut tampak pada keterbatasan informasi dan kesiapan administratif warga (misalnya dokumen waris, riwayat penguasaan, dan kejelasan batas), serta belum adanya pedoman tertulis desa untuk pendataan, verifikasi, dan pendampingan PTSL.  Pengabdian ini berfokus pada peningkatan pemahaman masyarakat dan penguatan kapasitas kelembagaan desa dengan pendekatan problem based approach dan kerangka Participatory Action Research (PAR).  Tahapan pelaksanaan meliputi koordinasi awal dan observasi, penyuluhan hukum berbasis ceramah interaktif disertai tanya jawab serta konsultasi kasus pada 1 Oktober 2025, diskusi lanjutan dengan perangkat desa, dan penyusunan draf Peraturan Desa (Perdes) tentang Tata Kelola Pelaksanaan PTSL. Hasil kegiatan menunjukkan meningkatnya literasi warga mengenai urgensi sertifikat, komponen data fisik dan yuridis, alur administrasi PTSL, serta solusi praktis atas persoalan dokumen hilang, tanah warisan, dan batas tidak jelas; kegiatan juga membantu meluruskan miskonsepsi terkait isu biaya. Pada level kelembagaan, draf Perdes menyediakan pedoman kerja yang lebih terstruktur, termasuk pembentukan tim pelaksana, mekanisme pendataan dan verifikasi, serta alur koordinasi desa BPN sehingga berpotensi memperkuat akuntabilitas layanan pertanahan dan mendukung keberlanjutan PTSL. Simpulannya, sinergi edukasi hukum dan penyusunan regulasi lokal efektif meningkatkan kesiapan administratif masyarakat sekaligus memperkuat tata kelola pertanahan desa.